An Analysis of Using Youtube Videos in Teaching Writing Competency in Seven Grade at SMPN 2 Singaraja - Fridayani, Kadek Budi; Paramartha, A.A. Gede Yudha; Wahyuni, Luh Gede Eka (STKIP AGAMA HINDU SINGARAJA, 2024)
This research aims to analyze the use of YouTube videos and the problems teachers face when using YouTube videos in teaching writing to seventh grade students at SMP N 2 Singaraja. The method used is a descriptive research method that focuses on data-based problem solving, data presentation, and data completeness. The techniques used to obtain data are observation and interviews, using observation sheets and interview guidelines through your own research. This research was carried out at SMP N 2 Singaraja with an English teacher and used two classes, namely: VII 1 and VII 2. In the observation sheet, an English teacher used four stages of writing, namely: pre-writing, compiling, revising and editing. In the interview guide there are two indicators that are problematic, namely: Teacher teaching skills and teacher teaching habits. In the first indicator, the teacher's lack of ability to manage teaching time means that the learning process becomes less effective. In the second indicator, teachers do not prepare the learning media needed by students. That is the result of research that there are still many techniques and ways to apply the four stages of teaching writing using YouTube videos.